PELAKSANAAN PENDAMPINGAN TERHADAP ANAK KORBAN KEKERASAN SEKSUAL OLEH LEMBAGA BURANGIR DI KOTA PADANGSIDIMPUAN - Rinda Fransiska Surya Uli (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
Cases of sexual violence against children can be likened to an iceberg, of which only a small number are reported while most are not reported. The stigma in society that views sexual violence as shameful makes victims afraid to report. Integrated handling of cases of sexual violence against children to ensure the fulfillment of children's rights is very important. This research aims to describe the implementation of assistance to child victims of sexual violence carried out by the Burangir Institute. The type of research used in this study is descriptive qualitative research. The data collection technique used observation, documentation and interviews. Data validity is seen by using data triangulation techniques, while data analysis goes through three processes, namely data reduction, data presentation and conclusion drawing. The results showed that the implementation of assistance to child victims of sexual violence by the Burangir Institute began with the establishment of a relationship of trust, followed by data collection and diagnosis of the child's mental health condition. Plans and interventions included emotional support, provision of information and legal education, monitoring the legal process, and access to support resources. Evaluation is used to assess the effectiveness of the assistance. Finally, the termination stage is conducted. Then, in the implementation of mentoring at the Burangir Institute, there are supporting factors and obstacles that affect the mentoring process. Keywords: Accompaniment, Children, Child sexual abuse.